Revistas, libros y bibliotecas : circulación, recepción y apropiación de textos higienistas en Chile (1869-1900) - Enrique Fernández Domingo (Les Cahiers ALHIM)
Based on the study of European and American medical publications that address hygienist issues during the last third of the 19th century and the libraries of Chilean institutions linked to hygienist practices, this article addresses the issue of circulation and reception of discourse hygienist in Chile.